In-situ stress measurements by hydraulic fracturing and its implication on coalbed methane development in Western Guizhou, SW China. (September 2016) - Xu, Hongjie; Sang, Shuxun; Yang, Jingfen; Jin, Jun; Hu, Youbiao; Liu, Huihu; Ren, Ping; Gao, Wei
Highlights: Stress filed type versus depth in Western Guizhou of China was discussed. The relationship of stress, burial depth and the permeability of coal reservoir were built. Control mechanism from in-situ stress on coal permeability was revealed. Abstract: Based on data independently measured and collected within depth from 135.9 to 1243.6 m in Western Guizhou, SW China, the distribution of in-situ stress was analyzed systematically. Maximum horizontal principal stress ( σHmax ), minimum horizontal principal stress ( σHmin ), vertical stress ( σv ) and lateral pressure ratio variations with depth were obtained by regression analysis. Results show that the growth rate of horizontal stresses is higher than that of vertical ones. Three types of stress field distribution have been noted that σv ⩾ σHmax ⩾ σHmin mainly occurs in shallow and intermediate to deep coal seams (<400 m and 600–1000 m), the σHmax ⩾ σv ⩾ σHmin mainly occurs in deep and shallow to intermediate coal seams (400–600 m and >1000 m). The ratio of maximum and minimum horizontal principal stress versus depth shows linear relationships with a correlation coefficient of 0.77 and 0.85, separately. The ratio of the maximum horizontal principal stresses to vertical stress is usually between 0.5 and 2.0 in coal seams, and decreases as the depth increases and approaches 1.0. The coefficient of average lateral stress versus depth ( λ ) is also illustrated, which shows a wide range at shallow sites from 0.48 to 1.80, and then gradually decreases to a fixed value as the depth increases. Coal permeability obtained during injection/falloff tests shows that the permeability is damaged with a trend difference under a depth of 550–750 m for the in-situ stress belting change and other reasons.